Evaluating the Implementation of the Birth Planning and Complication Prevention Program among Third-Trimester Pregnant Women: A Scoping Review - Mohammad Hakimi; Farida Kartini; Viana Remiciadas Dores Dos Reis (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: The maternal mortality rate (MMR) in Timor-Leste remains among the highest in Southeast Asia and continues to pose a significant public health challenge, particularly during the third trimester of pregnancy. Birth Planning and Complication Prevention (P4K) programs are essential strategies to reduce preventable maternal complications and improve birth preparedness. Method: A scoping review was conducted following the PRISMA-ScR framework. The review process included five stages: identifying the research question, searching relevant literature, selecting eligible studies, charting data, and summarizing and reporting the findings. Articles were retrieved from major databases and included studies published between 2016 and 2025 that examined BPCR/P4K implementation in pregnant women. Result: The findings indicate that birth preparedness is influenced by multiple determinants, including individual factors (maternal knowledge, parity, and pregnancy intention), social support from family and community, and the quality of antenatal care (ANC) services. In addition, effective detection and monitoring of obstetric risks during the third trimester play a critical role in improving preparedness and preventing complications. However, overall implementation of P4K remains suboptimal in several settings. Conclusion: Strengthening ANC education, enhancing family and community support systems, and optimizing third-trimester risk screening and monitoring are key strategies to improve the effectiveness of P4K implementation. These efforts are essential to reduce maternal complications and contribute to the reduction of maternal mortality in low-resource settings such as Timor-Leste